Pseudomonas rhizophila S211, a New Plant Growth-Promoting Rhizobacterium with Potential in Pesticide-Bioremediation - Hassen, Wafa; Neifar, Mohamed; Cherif, Hanene; Najjari, Afef; Chouchane, Habib; Driouich, Rim C.; Salah, Asma; Naili, Fatma; Mosbah, Amor; Souissi, Yasmine; Raddadi, Noura; Ouzari, Hadda I.; et al. (Frontiers in Microbiology, 2018)
A number of Pseudomonas strains function as inoculants for biocontrol, biofertilization, and phytostimulation, avoiding the use of pesticides and chemical fertilizers. Here, we present a new metabolically versatile plant growth-promoting rhizobacterium, Pseudomonas rhizophila S211, isolated from a pesticide contaminated artichoke field that shows biofertilization, biocontrol and bioremediation potentialities. The S211 genome was sequenced, annotated and key genomic elements related to plant growth promotion and biosurfactant synthesis were elucidated. S211 genome comprises 5,948,515 bp with 60.4% G+C content, 5306 coding genes and 215 RNA genes. The genome sequence analysis confirmed the presence of genes involved in plant-growth promoting and remediation activities such as the synthesis of ACC deaminase, putative dioxygenases, auxin, pyroverdin, exopolysaccharide levan and rhamnolipid biosurfactant (BS). BS production by P. rhizophila S211 grown on olive mill wastewater based media was effectively optimized using a central-composite experimental design and response surface methodology. The optimum conditions for maximum BS production yield (720.80 ± 55.90 mg/L) were: 0.5% (v/v) inoculum size, 15% (v/v) olive oil mill wastewater and 40°C incubation temperature at pH 6.0 for 8 days incubation period. Biochemical and structural characterization of S211 BS by chromatography and spectroscopy studies suggested the glycolipid nature of the BS. P. rhizophila rhamnolipid was stable over a wide range of temperature (40-90°C), pH (6 to 10), and salt concentration (up to 300 mM NaCl). Due to its low-cost production, emulsification activities and high performance in solubilization enhancement of chemical pesticides, the indigenous BS-producing PGPR S211 could be used as a promising agent for environmental bioremediation of pesticide-contaminated agricultural soils.